Local Government Councils Perfomance and the Quality of Service Delivery in Uganda Kamuli District Council Score-Card 2008/2009service Delivery In Uganda Local Government Councils - Tucungwirwe, Francis; Ssemakula, Eugene Gerald; Tamale, Lilian Muyomba; Merewoma, Leo Waibi; Kahinda, Catheline (ACODE Policy Research Paper Series, 2010)
"The findings from the district Score-Card partly explain the quality of service delivery in Kamuli District. A number of structural, policy and operational factors that impinge on the quality of services have been identified from the assessment. While most councilors maybe aware of their duties, roles and obligations as stipulated in the Local Government Act, commitment to their implementation and realization was not forthcoming. In addition, there was poor documents and record keeping on the part of the political leaders and a discernable detachment from the electorate. The following are specific recommendations that the council can undertake to improve its performance and that of its councilors as a means of improving service delivery at the district level."